2020
DOI: 10.11591/ijece.v10i3.pp2773-2778
|View full text |Cite
|
Sign up to set email alerts
|

Design and implement a new mechanism for audio, video and screen recording based on WebRTC technology

Abstract: Many years ago, Flash was essential in browsers to interact with the user media devices, such as a microphone and camera. Today, Web Real-Time Communication (WebRTC) technology has come to substitute the flash, so browsers do not need the flash to access media devices or establish their communication. However, WebRTC standards do not express precisely how browsers can record audios, videos or screen instead of describing getUserMedia API that enables a browser to access microphone and camera. The prime objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In [20,21], indicated that videoconferencing using WebRTC technology is required as long as, different hospitals, economic and social levels, language practice, and companies have needed videoconferencing to interact with people [22][23][24]. However, WebRTC lakes high-end of video conferencing [25]. Therefore, many types of research have designed WebRTC video calls using XMLHttpRequest (XHR).…”
Section: Related Workmentioning
confidence: 99%
“…In [20,21], indicated that videoconferencing using WebRTC technology is required as long as, different hospitals, economic and social levels, language practice, and companies have needed videoconferencing to interact with people [22][23][24]. However, WebRTC lakes high-end of video conferencing [25]. Therefore, many types of research have designed WebRTC video calls using XMLHttpRequest (XHR).…”
Section: Related Workmentioning
confidence: 99%
“…Web Real-Time Communication (WebRTC) framework offers the ability of direct interactive communication for audio, video and data between two web browsers (peer-to-peer) [1]. This technology does not need to registration, downloading, installation, external software (plugins), license, etc [2]. Also, it describes the aspects of media transport and identifies how the Real-Time Transport Protocol (RTP) is employed in the WebRTC context [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the user needs to use the webcam for an example, he is requested to allow the use of this resource. It often happens, when is requested to establish a video stream connection using the WebRTC (Web Real-Time Communication) framework, implemented by the latest browsers affording multi-video-streaming channels between peers (HA et al, 2020;EDAN;MAHMOOD, 2020;GARCÍA et al, 2020).…”
Section: Web Server Applicationmentioning
confidence: 99%